Pregravid preparation of women with polycystic ovary syndrome. - Г. О. Ісламова (Publishing House TRILIST, 2020)
Polycystic ovary syndrome (PCOS) is a significant component in the structure of diseases that cause female infertility, and the most common cause of ovarian dysfunction in women of reproductive age. This disease significantly increases the risk of miscarriage, the development of preterm labor, and increases the incidence of perinatal complications such as gestational diabetes, fetal macrosomia, and gestational hypertension. A comparative prospective study was conducted with 60 patients of reproductive age suffering from PCOS (phenotype A) and having an increased body mass index. At the beginning of the study, all patients received recommendations about an individually selected reduction diet, a set of physical exercises, and adherence to an eight-hour night's sleep regimen. By random sampling, the patients were divided into 2 groups of 30 people each. For 6 months, the patients of the main group received twice a day 1 sachet Miofolik. 1 sachet contains: myo-inositol 2000 mg, vitamin B12 5 μg, folic acid ((68)-5-methyltetrahydrofolate) 200 μg. Patients in the control group did not receive drug support, observing dietary recommendations and performing a set of physical exercises only. An analysis of the results of the study of the drug Myofolik in women with PCOS indicates its positive complex effect on metabolic disorders (improved lipid and carbohydrate metabolism), decreased hyperandrogenia, restoration of the ovulatory cycle (decreased levels of LH and LH / FSH, increased levels of estradiol, progesterone), which accordingly significantly increases the chances of pregnancy. The results of the study allow us to recommend the drug Miofolik for pregravid preparation in patients with polycystic ovary syndrome.